Loneliness and Behavioral Changes During the COVID-19 Pandemic. (17th December 2021) - Li, Qiwei; Drazich, Brittany; Hladek, Melissa; Samuel, Laura; Latkin, Carl; Boyd, Cynthia; Cudjoe, Thomas
Abstract: Concerns for the health impact of loneliness, a risk factor for morbidity and mortality, have risen amid the COVID-19 pandemic. However, relationships between loneliness and behavioral changes remains unclear. Utilizing data from the National Health and Aging Trends Study COVID-19 Supplement, we examine the cross-sectional relationship between loneliness and self-reported increase in each of the following behaviors during the pandemic (n=2, 924): walking, vigorous activity, eating, use of alcohol and tobacco, watching television and sleeping. Adjusting for age, race, education, activity of daily living limitations, and chronic conditions, loneliness was significantly associated with a higher odds of more eating (odds ratio- OR: 1.42, confidence intervals-CI: 1.24, 1.62), sleeping (OR: 1.35, CI: 1.18, 1.56), and watching television (OR: 1.45, CI: 1.30, 1.61). These results indicate that during stressful times like our current pandemic, loneliness may lead to morbidity and mortality through sedentary behaviors.